A clinical-grade gene therapy vector for pharmacoresistant epilepsy successfully overexpresses NPY in a human neuronal cell line. (February 2018) - Patrício, Maria I.; Barnard, Alun R.; Green, Alexander L.; During, Matthew J.; Sen, Arjune; MacLaren, Robert E.
Abstract: Purpose: Epilepsy is a common neurological condition characterised by recurrent unprovoked seizures and often treatable with appropriate medication. However, almost 30% of cases are pharmacoresistant and while a proportion of these may be amenable to resective surgery, a gene therapy approach could be an attractive alternative option. Neuropeptide Y (NPY) has anticonvulsant and anti-epileptogenic properties in animal models of temporal lobe epilepsy when delivered by an adeno-associated viral (AAV) vector. Here we sought to demonstrate successful secretion of NPY from AAV-transduced human neuronal cells, which would be essential in planning any clinical trial. Methods: A human neuroblastoma cell line (SH-SY5Y) was used to assess in vitro whether an AAV vector manufactured to clinical-grade protocols would be effective at transducing these cells to express NPY. Optimal transduction efficiency was first achieved with retinoic acid and tetradecanoylphorpol-13-acetate (TPA) treatment, prior to expose to AAV1-green fluorescent protein (GFP) reporter vector, AAV1-NPY therapeutic vector or sham treated with no vector. Levels of NPY in cell supernatants were determined using two antibody-based methods Results: We found that the levels of NPY released into the cell culture media supernatant, and protein extracts of the cell pellet, were significantly higher following exposure to AAV1-NPY than when compared to either a control GFP reporter vector (AAV1-GFP) or sham treated controls. Conclusion: This first demonstration that an AAV-NPY construct can successfully transduce human neuronal cells supports the pre-clinical development of a clinical trial using AAV-based NPY for pharmacoresistant epilepsy.